Reflexivity as Key Element Specificity of Object of Research of Personality Psychology - Vlasyuk, Dmytro (Psychological Prospects Journal, 2013)
Individual reflection as a unique characteristic of personality is a key element of the specificity of the object of the research of personality psychology in relation to objects of other scientific disciplines. This difference to a large extent determines the specificity of the scientific paradigm and research methodology of personality psychology.